2006
DOI: 10.1089/tmj.2006.12.289
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Services to Improve Nonadherence: A Placebo-Controlled Study

Abstract: The objective of this study was to test whether a telehealth intervention could improve the compliance with continuous positive airway pressure (CPAP) by patients with sleep apnea. These patients had been nonadherent for the initial 3 months of therapy even after receiving the initial standard and then supplemental audiotaped/videotaped patient education for adhering to CPAP nightly. The materials and methods included a randomized testing of experimental and placebo interventions. Interventions were delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 24 publications
1
78
0
2
Order By: Relevance
“…It is possible that, in the future, new technologies such as telemedicine will have a key role in these programmes [48,49], contributing to an increase in adherence [50]. In this regard, other recent studies have shown similar results to those presented in this work, supporting the validity of our approach [25,51,52].…”
Section: Group B N=22supporting
confidence: 84%
“…It is possible that, in the future, new technologies such as telemedicine will have a key role in these programmes [48,49], contributing to an increase in adherence [50]. In this regard, other recent studies have shown similar results to those presented in this work, supporting the validity of our approach [25,51,52].…”
Section: Group B N=22supporting
confidence: 84%
“…Most systems use cards (smart cards or SD cards), memory sticks, or wireless transmission. Several studies (64,65) have demonstrated that these transmission systems may be better than routine practice (see the online supplement for details about these studies). Although wireless transmission of CPAP adherence data is the future, a major problem with wireless systems is having the resources to retrieve the data.…”
Section: Cpap Adherence Tracking Transmission Systemsmentioning
confidence: 99%
“…[39][40][41] Being able to predict a patient's "risk" for poor CPAP adherence early, ideally at the point of CPAP therapy initiation, may be useful in targeting "high-risk" patients for these interventions.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%